Soluble urokinase plasminogen activator receptor (suPAR) plasma concentration is reduced using minimized extracorporeal circulation : results of a secondary analysis of a prospective observational study - Zajonz, Thomas S.; Edinger, Fabian; Götze, Juliane; Markmann, Melanie; Sander, Michael; Koch, Christian; Schneck, Emmanuel; Justus Liebig University Giessen (My University, 2025)
Background: Minimized extracorporeal circulation (miECC) was developed to mitigate the adverse effects of cardiopulmonary bypass (CPB), yet its impact on soluble Urokinase plasminogen activator receptor (suPAR) is unclear. SuPAR has been linked to adverse outcomes, including acute kidney injury (AKI). This study investigated perioperative suPAR kinetics in patients undergoing cardiac surgery with miECC or conventional CPB (cCPB) and explored its association with AKI, postoperative delirium (POD), and infections. Methods: This study is a secondary analysis of an observational cohort of 79 cardiac surgical patients. It evaluates perioperative suPAR levels and their association with the type of CPB used (miECC vs. cCPB) and postoperative adverse outcomes, including POD, AKI, and infections. Statistical analyses included repeated measures ANOVA, Wilcoxon tests, logistic regression, and ROC curve analysis to assess the predictive value of suPAR for these outcomes. Results: During surgery, suPAR significantly increased to higher Levels with the use of cCPB compared to miECC (p = 0.027; odds ratio of 0.69 [0.57–0.84], p < 0.001). The use of miECC was an independent influencing factor on suPAR (−0.41 ± 0.1; p < 0.001). Regardless of the type of CPB, suPAR levels differed significantly between patients with and without kidney damage (n = 25; no AKI: 1.6 [1.1–2.0], AKI: 1.7 [1.3–2.4], p < 0.001). Multivariate regression analysis showed that AKI was an independent influencing factor on suPAR (−0.49 ± 0.1; p < 0.001). SuPAR demonstrated only low predictive value for AKI and could not predict POD. Conclusions: This study provides evidence that miECC is associated with lower intraoperative suPAR levels, suggesting a reduced inflammatory response compared to cCPB. While suPAR levels were significantly higher in patients with AKI, their predictive value for AKI remains limited. Furthermore, suPAR did not predict POD but was elevated in patients with pneumonia.
Keywords: ddc:610